Comparison of the information content of the notes on the accounts between information technology services and sports activities - Kerezsi, Dóra (International Journal of Engineering and Management Sciences, 2020)
Annual accounting statements are an important source of information within business relations amongst companies. However, it should be noted that due to their aggregate nature, the necessary information and through that the necessary knowledge can only be obtained from the two fundamental parts of the annual statements (balance sheet and profit and loss account) if the notes on the account contains the information that contributes to the more comprehensive interpretation of the other part of the annual statement. Beyond that, the notes to the financial statement have to help the presentation of a reliable and realistic overall image. In the notes to the financial statement, depth and detail of the disclosed information are not specifically stated, therefore their professional evaluation is left to the given enterprise. My basic purpose is to illustrate a comparison of the information content of the notes on the accounts between information technology services and sports activities. By means of text mining, we analyse the extent to which the notes on the accounts are in conformity with the Accounting Act.